Distribution of Bioaerosols in Association With Particulate Matter: A Review on Emerging Public Health Threat in Asian Megacities - Shammi, Mashura; Rahman, Md Mostafizur; Tareq, Shafi Mohammad (Frontiers in Environmental Science, 2021)
Occurrences and exposure to high levels of microbial bioaerosols such as pathogenic bacteria, fungi, fungal spores, and viruses can be linked to the deterioration of the environment and public health. This study aimed to review the results available for the unusual bioaerosol distribution scenario in the Asian regions. The amount of bioaerosol load and their environmental behavior in the atmosphere is heavily influenced by air pollution such as haze, fog, dust, and particulate matter (PM) and thus strongly affect the air quality index (AQI). Human factors such as heavy traffic, overcrowds, and biomass burning also affected the prevalence/ or occurrences of bioaerosols in the atmosphere. Seasonal/temporal and diurnal variation was significantly observed from these studies and in the case of South Asia, post-monsoon and winter months were incredibly concentrated with pathogenic bioaerosols. Many human infections, for example, pneumonia, tuberculosis, brucellosis, anthrax, and query fever (Q-fever), are linked to pathogenic bacterial bioaerosols. Respiratory diseases such as asthma and chronic pulmonary obstructiveness are related to fungal bioaerosols, spores, and viral infections. To facilitate the testing and monitoring appraisal of airborne bioaerosols, artificial intelligence, deep neural networks, and machine learning can be used to develop real-time PCR-based bioaerosol-sensors. Moreover, mobile apps and compatible electronic gadgets can be developed for the city dwellers to real-time monitor the concentration of bioaerosols in the air they are breathing.